Power generation device, method for producing magnetic hard viscoelastic material, and method for using the power generation device

A magnetorheological material with ferromagnetic particles in a polymeric viscoelastic material generates induced current through deformation, addressing the weight and size issues of existing devices, enabling efficient low-frequency vibration energy harvesting.

JP7615446B2Active Publication Date: 2025-01-17KRI INC +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2018131172
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2017-07-12
Filing Date
2018-07-11
Publication Date
2025-01-17
Estimated Expiration
2038-07-11

AI Technical Summary

Technical Problem

Existing power generation devices using magnetic elastomers require external permanent magnets, leading to increased weight and size, and existing magnetorheological materials are not optimized for power generation applications.

Method used

A magnetorheological material with ferromagnetic particles, primarily composed of rare earth elements, dispersed in a polymeric viscoelastic material, which generates an induced current through deformation, eliminating the need for external magnets and allowing for a lightweight, flexible power generation device.

Benefits of technology

The device achieves high power generation performance with a compact, flexible structure, capable of converting low-frequency vibrations into electricity efficiently.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007615446000001
    Figure 0007615446000001
  • Figure 0007615446000002
    Figure 0007615446000002
  • Figure 0007615446000003
    Figure 0007615446000003
Patent Text Reader

Abstract

To obtain a compact light-weight power generation device by using a viscoelastic body in which ferromagnetic particles are dispersed in a viscoelastic material.SOLUTION: A power generation device includes: a magnetic viscoelastic body 1 having magnetic coercive force which is obtained by forming a magnetic hard viscoelastic material in which ferromagnetic particles in a magnetization state are dispersed in a viscoelastic material; magnetic viscoelastic body deformation means 2 for deforming the magnetic viscoelastic body 1 under external force; and induction current generation means 3 for generating an induction current in the interior by a magnetic flux whose space distribution changes due to deformation of the magnetic viscoelastic body 1. The power generation device also includes output means 4 for outputting an induction current generated in the induction current generation means 3. The ferromagnetic particles are composed mainly of rare earth elements.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a power generating device that generates power when subjected to an external force, to a viscoelastic material used in the power generating device, and to a method for using the power generating device. [Background technology]

[0002] Recently, a functional material called magnetic elastomer (a viscoelastic material with magnetism) has been attracting attention. This material is made by dispersing and hardening magnetic particles such as iron powder in a viscoelastic material such as silicone gel, and has both viscoelastic and magnetic properties. This type of functional material has a change in elastic modulus and can be induced to deform when subjected to an external magnetic field, so research into its applications such as soft actuators and vibration absorbers is being actively conducted. One application of this type of functional material that has attracted attention is vibration power generation using Faraday's electromagnetic induction (Non-Patent Document 1).

[0003] Meanwhile, the inventors have proposed a functional material that has a coercive force in itself, which they call a "magnetorheological material," for application to soft actuators and vibration absorbers (Patent Document 1). This functional material has ferromagnetic particles uniformly dispersed within a viscoelastic material, so no matter where you cut it, it has the same magnetic properties (coercive force).As a result, it can be sliced ​​thinly, and can be used as a viscoelastic thin-film permanent magnet in applications that require large deformation, such as artificial muscles. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2016-152337 A [Non-patent literature]

[0005] [Non-Patent Document 1] Fujio Tsumura et al., Development of an inverse magnetostrictive power generation device using magnetic fine particle dispersed elastomer, Powder and Powder Metallurgy, Powder and Powder Metallurgy Press, Vol. 61, No. 4, April 2014, pp. 193-198 Summary of the Invention [Problem to be solved by the invention]

[0006] However, in the magnetic elastomer disclosed in Non-Patent Document 1, the magnetic particles are mainly composed of iron, so when used in a power generating device, a permanent magnet (external permanent magnet) is required to magnetize the magnetic particles. This makes the power generating device heavy and large. Therefore, there is room for improvement.

[0007] On the other hand, the technology disclosed in Patent Document 1 merely proposes applications for soft actuators and vibration absorbers, taking advantage of the ease of shape selection and ease of deformation, and there is room for further study on its use as a power generation device.

[0008] In view of the above situation, a main object of the present invention is to obtain a power generating device having a small and lightweight structure by using a viscoelastic body in which ferromagnetic particles are dispersed, and a further object is to obtain a viscoelastic material that can be suitably used for the power generating device, and to propose suitable uses for the power generating device. [Means for solving the problem]

[0009] A first characteristic configuration of the power generating device according to the present invention is a magnetic viscoelastic body having a coercive force, the magnetic viscoelastic body being formed by molding a magnetically hard viscoelastic material in which magnetized ferromagnetic particles are dispersed within the viscoelastic material; a magnetic viscoelastic body deformation means for deforming the magnetic viscoelastic body by receiving an external force; an induced current generating means for generating an induced current therein by a magnetic flux whose spatial distribution changes due to the deformation of the magnetic viscoelastic body; an output means for outputting the induced current generated by the induced current generating means, the ferromagnetic particles are ferromagnetic particles mainly composed of rare earth elements, The viscoelastic material is a polymeric material that exhibits viscoelasticity at room temperature.

[0010] This power generation device is configured with a magnetic viscoelastic body, a magnetic viscoelastic body deformation means, an induced current generation means, and an output means. As a result, when the magnetic viscoelastic body is deformed by an external force via the magnetic viscoelastic body deformation means, an induced current is induced in the induced current generation means in accordance with the deformation. Then, this induced current can be extracted and utilized by the output means.

[0011] Here, by using rare earth as the main component of the ferromagnetic particles, it is possible to make the coercive force exhibited by the magnetorheological body sufficiently high, and at the same time, by using a polymeric material exhibiting viscoelasticity at room temperature as the viscoelastic material, it is possible to maintain the high deformability at room temperature and generate a large deformation. As a result, the magnetic flux around the magnetorheological body changes significantly, and a lightweight and small power generating device can be constructed with a simple configuration that essentially includes only the magnetorheological body, the magnetorheological body deformation means, the induced current generating means, and the output means. Furthermore, since the magnetorheological body can be molded into any shape, the power generating device of the present invention can be used in a very wide range of applications. The concept of "magnetically hard" in the present invention means that the material has a large coercive force and has the properties of a permanent magnet.

[0012] A second characteristic configuration of the power generating device of the present invention is The ferromagnetic particles are neodymium magnet particles with an average particle size of 100 μm or less, The induced current generating means is a coil.

[0013] Neodymium magnet particles have a main phase of Nd 2 Fe 14B, which makes for a particularly strong magnet. Furthermore, by making the average particle size 100 μm or less when dispersing it in the viscoelastic material, it becomes possible to disperse it almost evenly in the material, which is easy to use in the subsequent molding. Furthermore, by configuring the induced current generating means with a coil, it becomes possible to extract the induced current generated in response to the change in magnetic flux around the magnetic viscoelastic body in the simplest and most inexpensive way.

[0014] A third characteristic configuration of the power generating device of the present invention is The blending ratio of the ferromagnetic particles to the viscoelastic material is within a range of 40 to 90 wt % by weight.

[0015] By adopting this configuration, a magnetorheological material having the right magnetic properties and viscoelasticity can be obtained to construct a power generating device according to the present invention. If the weight ratio is less than 40wt%, the ferromagnetic particles tend to be insufficient, and the surface magnetic flux density that is normally preferably obtained for a given volume may not be sufficiently ensured. On the other hand, if the weight ratio exceeds 90wt%, the magnetorheological material, which is a dispersion / mixture, becomes hard and the deformation amount is easily insufficient. Furthermore, this weight percentage is preferably 40wt% to 70wt%. By setting it to 70wt% or less, the amount of ferromagnetic particles can be limited, and the required coercive force can be obtained while maintaining the viscoelasticity of the material.

[0016] The magnetic viscoelastic material that constitutes the power generation device explained so far (referred to as "magnetic hard viscoelastic material" in this invention) is a material with viscoelasticity and a high coercive force. It is preferable to manufacture the magnet (having magnetic force as a permanent magnet and residual magnetic flux density) by the following method.

[0017] That is, a fourth characteristic configuration of the power generating device of the present invention is The magnetic hard viscoelastic material can be a material produced by a production method including a dispersion step of dispersing ferromagnetic particles having an average particle size of 100 μm or less, mainly composed of rare earth, in a viscoelastic material before a hardening treatment to obtain a primary precursor, a hardening step of hardening the primary precursor obtained in the dispersion step to obtain a secondary precursor, and a magnetization step of applying a uniform magnetic field of 1.5 T or more to the secondary precursor obtained in the hardening step to magnetize the ferromagnetic particles.

[0018] Through the dispersion process, hardening process and magnetization process, the ferromagnetic particles dispersed in the viscoelastic material are successfully magnetized, and a permanent magnet (magnetically hard viscoelastic material) with strong coercive force, residual magnetic flux density and viscoelasticity can be used to obtain a power generation device with excellent performance.

[0019] Furthermore, a fifth characteristic configuration of the power generating device of the present invention is The ferromagnetic particles have magnetic anisotropy.

[0020] By adopting this configuration, when the same amount of ferromagnetic particles are dispersed in a viscoelastic material and formed into a compact, the magnetic flux around the magnetic viscoelastic body can be made stronger (the surface magnetic flux density becomes higher), and the power generation device can have higher performance than when ferromagnetic particles that have virtually no magnetic anisotropy are used. As a result, the amount of ferromagnetic particles can be reduced, and the power generation device can be made smaller.

[0021] The first characteristic feature of the method for producing a magnetic hard viscoelastic material of the present invention is as follows: a dispersion step of dispersing ferromagnetic particles having an average particle size of 100 μm or less, mainly composed of rare earth elements, in a viscoelastic material before a curing treatment to obtain a primary precursor; The present invention is characterized in that it includes a magnetization hardening process in which a uniform magnetic field is applied to the primary precursor obtained in the dispersion process to magnetize the ferromagnetic particles, and a hardening process in which the primary precursor is hardened, the magnetization hardening process being carried out simultaneously or sequentially.

[0022] In this configuration, the process of obtaining the primary precursor through the dispersion process is the same as the example described above. That is, the primary precursor is in a state where ferromagnetic particles are dispersed in the viscoelastic material before the curing process, and in fact has fluidity. As a result, the ferromagnetic particles can move and change their position to a certain extent within the viscoelastic material. As described above, in this primary precursor, the particle diameter of the ferromagnetic particles is 100 μm or less, so that it is possible to make the particles uniformly dispersed within the viscoelastic material by a dispersion process such as stirring. In addition, since the particles are mainly composed of rare earths, they can hold a strong magnetic force.

[0023] In the magnetization and hardening process which follows the dispersion process, the magnetization treatment and hardening treatment are carried out simultaneously or sequentially. That is, when the primary precursor is placed in a magnetic field and magnetized while the ferromagnetic particles are in a state where they can move and change their position to some extent, many ferromagnetic particles are magnetized individually, and a columnar structure is generated in which many of these particles are aligned in the direction of the magnetic flux. Figures 6 and 15 show the columnar structure. The columnar structure can be maintained by hardening treatment. As a result, by carrying out this manufacturing method, it is possible to obtain a magnetically hard viscoelastic material that has viscoelasticity and high coercivity in terms of the volume occupied by it. As will be described later, this specification presents the results of investigations into both magnetically isotropic particles, in which the magnetic moment of the particle itself has no directionality, and magnetically anisotropic particles, in which the magnetic moment has directionality, as ferromagnetic particles. Here, the primary precursor resulting from the dispersion step becomes isotropic regardless of whether the particles are magnetically isotropic or magnetically anisotropic. If the primary precursor is hardened and then magnetized, the resulting product will be a magnetically hard viscoelastic material that maintains isotropy. On the other hand, if the primary precursor is hardened while being magnetized, the columnar structure described above can be obtained, resulting in a magnetically hard viscoelastic material with anisotropy.

[0024] The second characteristic feature of the method for producing the magnetic hard viscoelastic material is as follows: The magnetization hardening process includes a preliminary magnetization hardening completion process in which the magnetization treatment and the hardening treatment are performed simultaneously, and a main magnetization process in which a magnetic field stronger than the magnetization magnetic field in the preliminary magnetization hardening completion process is applied to the preliminary magnetization hardening completed body obtained through the preliminary magnetization hardening completion process to complete the magnetization of the ferromagnetic particles.

[0025] In this configuration, the magnetization hardening process includes two processes, a preliminary magnetization hardening completion process and a main magnetization process, in which the primary precursor is placed in a certain degree of magnetic field to ensure the orientation state (columnar structure) of the ferromagnetic particles. If an even higher magnetization state is desired, the main magnetization process is carried out to achieve the desired high magnetization state. As a result, it is possible to obtain a magnetically hard viscoelastic material in which the ferromagnetic particles are arranged in the viscoelastic material and in which the amount of magnetization is extremely high.

[0026] The third characteristic feature of the method for producing a magnetic hard viscoelastic material of the present invention is as follows: The ferromagnetic particles have magnetic anisotropy.

[0027] By adopting this configuration, when the same amount of ferromagnetic particles is dispersed in a viscoelastic material and formed into a molded body, the magnetic field around the magnetic viscoelastic body can be made stronger, and the power generation device can have higher performance than when ferromagnetic particles that have virtually no magnetic anisotropy are used.

[0028] The magnetically hard viscoelastic material produced by the magnetically hard viscoelastic material manufacturing method having the first to third characteristic configurations is molded into a predetermined shape, and the molded body is used as a magnetic viscoelastic body for a power generation device, thereby obtaining a power generation device with high power generation performance.

[0029] Now, since the power generation device described so far is made up mainly of a flexible magnetic viscoelastic material, a preferred method of use thereof is to generate power by periodically deforming the magnetic viscoelastic material through an external force that fluctuates at a frequency of 50 Hz or less via the magnetic viscoelastic material deformation means.

[0030] This is because the magnetoelastic body behaves as a viscoelastic body and is therefore capable of responding to external force fluctuations, particularly at low frequencies. [Brief description of the drawings]

[0031] [Figure 1] Diagram showing the configuration of a power generation device [Diagram 2] FIG. 1 is a diagram showing a manufacturing process of a magnetic viscoelastic body according to a first manufacturing method. [Diagram 3] FIG. 1 is a diagram showing the dispersion state of ferromagnetic particles in a magnetic hard viscoelastic material obtained by the first manufacturing method. [Figure 4] FIG. 1 is a diagram showing a manufacturing process of a magnetic viscoelastic body according to a second manufacturing method. [Diagram 5] An explanatory diagram of the magnetization hardening treatment device used in the manufacturing process of the second manufacturing method [Figure 6] FIG. 1 shows the columnar structure of the magnetic hard viscoelastic material obtained by the second manufacturing method. [Figure 7] A diagram showing the test equipment for power generation devices (magnetic viscoelastic materials) [Figure 8] Figure showing the power generation test results of a magnetic hard viscoelastic material using magnetically isotropic ferromagnetic particles. [Figure 9] Figure showing the power generation test results of a magnetic hard viscoelastic material using magnetically isotropic ferromagnetic particles. [Figure 10] Figure showing the power generation test results of a magnetic hard viscoelastic material using magnetically isotropic ferromagnetic particles. [Figure 11] Figure showing the power generation test results of a magnetic hard viscoelastic material using magnetically isotropic ferromagnetic particles. [Figure 12] A diagram showing the change in surface magnetic flux density before and after compression [Figure 13]Figure showing the power generation test results of a magnetic hard viscoelastic material using magnetic anisotropic ferromagnetic particles. [Figure 14] FIG. 1 is a schematic diagram showing the orientation of the magnetic moments of ferromagnetic particles in a magnetically hard viscoelastic material obtained by the first manufacturing method using magnetically anisotropic ferromagnetic particles. [Figure 15] FIG. 2 is a schematic diagram showing the orientation of the magnetic moments of ferromagnetic particles in a magnetically hard viscoelastic material obtained by the second manufacturing method using magnetically anisotropic ferromagnetic particles. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0032] The following will be described with reference to the drawings in the following order: 1. the configuration of the power generating device 100; 2. a manufacturing process for the magnetorheological body 1 used in the power generating device 100; and 3. power generation test results of the power generating device 100.

[0033] In this specification, two manufacturing methods ("first manufacturing method" and "second manufacturing method") are introduced for the material of the magnetic viscoelastic body 1 (magnetic hard viscoelastic material s in this invention), which is the main element constituting the power generating device 100.

[0034] Regarding the first manufacturing method and the second manufacturing method, the configuration of 1. the power generating device 100 is common. On the other hand, the manufacturing process of the magnetic viscoelastic body 1 used in 2. the power generating device 100 is different between the first manufacturing method and the second manufacturing method. Using these different manufacturing methods, ferromagnetic particles p, both of which have magnetic isotropic and magnetic anisotropic polarity, were examined. Regarding the power generation test results of 3. the power generating device 100, first, the results of manufacturing using the first manufacturing method and the second manufacturing method using a magnetic isotropic material are shown in 3.2.1, and the results of manufacturing using the first manufacturing method and the second manufacturing method using a magnetic anisotropic material are shown in 3.2.2.

[0035] The first manufacturing method is characterized in that the magnetically hard viscoelastic material s is manufactured in the following order: a. dispersing and mixing ferromagnetic particles p into a viscoelastic body e (dispersing step S1 described later), b. hardening and molding the mixture, which is the primary precursor (hardening step S2 described later), and c. magnetizing the ferromagnetic particles p (magnetizing step S3 described later).

[0036] The second manufacturing method is characterized in that the magnetically hard viscoelastic material s is manufactured by a) dispersing and mixing ferromagnetic particles p in a viscoelastic body e (dispersing step S10 described later), and b) simultaneously orienting and magnetizing the ferromagnetic particles p contained in the mixture which is the primary precursor, and hardening and molding the primary precursor, and further magnetizing the ferromagnetic particles p (magnetizing and hardening step S20 described later).

[0037] 1. Configuration of power generation device FIG. 1 shows the configuration of a power generating device 100 . The power generation device 100 is formed by molding a magnetically hard viscoelastic material s into a predetermined shape, and is configured to include a magnetic viscoelastic body 1 which itself has magnetic force, a magnetic viscoelastic body deformation means which deforms the magnetic viscoelastic body 1 when subjected to an external force, an induced current generating means which generates an induced current in response to the deformation of the magnetic viscoelastic body 1, and an output means which outputs the current generated in the induced current generating means.

[0038] 1, the magnetic viscoelastic body 1 is a molded body formed into a roughly cylindrical shape, and is configured to include plate-shaped external force transmission members 2 as magnetic viscoelastic body deformation means at both ends of the cylinder. In the illustrated example, the magnetic viscoelastic body 1 is deformed and compressed by an external force F applied downward to the external force transmission member 2. The amount of deformation can be a maximum of about 10 mm for the magnetic viscoelastic body 1 having a cylindrical diameter of 18 mm and a height of 18 mm, for example.

[0039] A coil (winding coil) 3 is disposed around the outer periphery of the magnetic viscoelastic body 1 as an induced current generating means, independent of the deformation of the magnetic viscoelastic body 1. In this configuration, when the magnetic viscoelastic body 1 is deformed by an external force, the magnetic flux around the magnetic viscoelastic body 1 changes with the deformation, generating an induced current in the coil 3. The generated current is output from both ends of the coil and utilized by an electrically connected load 5. Examples of the load 5 include a power storage device that stores the generated power, and a power consumption device that consumes the generated power. Therefore, the connection wire 4 connecting the coil 3 and the load 5 serves as the output means in the present invention.

[0040] As is clear from the above explanation, in the power generating device 100 of the present invention, the magnetorheological body 1 itself has magnetic force (has properties as a permanent magnet), so there is no need to provide an external magnet (not shown) as was necessary in the prior art. That is, the power generating device has a very simple structure that includes the magnetorheological body 1, magnetorheological body deformation means 2, and induced current generating means 3.

[0041] 2. Manufacturing of magnetorheological material In the test, the following materials were used as the viscoelastic material e and the ferromagnetic particles p. Viscoelastic material e is a polymeric material that exhibits viscoelasticity at room temperature, and in the example shown below, silicone gel (TSE3062 manufactured by Momentive Performance Materials Japan, Inc.) is used. Silicone gel hardens to a certain extent by adding a curing agent and heating it, but even after the hardening process, it returns to room temperature and retains its viscoelasticity.

[0042] The ferromagnetic particles p are ferromagnetic particles mainly composed of rare earth elements, and in this embodiment, neodymium magnetic powder available in Japan was used. It is a powder of neodymium magnet distributed as "NdFeB magnetic powder". In the embodiment shown below, the ferromagnetic particles p are magnetically isotropic and magnetically anisotropic, and the magnetically isotropic ones are described as "NdFeB magnetic powder isotropic" and the magnetically anisotropic ones are described as "NdFeB magnetic powder anisotropic". These "NdFeB magnetic powders" were available from, for example, Magnequench, Aichi Steel, Hitachi Metals, and Mitsubishi Materials. The "NdFeB magnetic powder isotropic" available from Magnequench is MQFP14-12-20000-089, and the "NdFeB magnetic powder anisotropic" is MQA38-14-20077-065.

[0043] FIG. 2 shows a manufacturing process of the magnetic viscoelastic body 1 according to the first manufacturing method, and FIG. 4 shows a manufacturing process of the magnetic viscoelastic body 1 according to the second manufacturing method. The manufacturing processes of these embodiments are examples of forming the magnetically hard viscoelastic material s into a suitable shape in conjunction with the production of the material s. That is, in the illustrated manufacturing processes, the magnetically hard viscoelastic body 1 is also formed in the hardening step. Therefore, in Fig. 2 and Fig. 4, for the sake of notation, the hardening step S2 or the preliminary magnetization hardening completion step S21 is shown as a forming step in parentheses.

[0044] 2.1 First manufacturing method As shown in FIG. 2, the manufacturing process of this embodiment follows the following sequence. a Dispersion process S1 Ferromagnetic particles p, mainly composed of rare earth and having an average particle size of 100 μm or less, are dispersed in a viscoelastic material e before hardening treatment to obtain a primary precursor.

[0045] b Curing process S2 The primary precursor obtained in the dispersion step S1 is cured to obtain a secondary precursor.

[0046] c Magnetization process S3 A uniform magnetic field of 1.5 T or more is applied to the secondary precursor obtained in the hardening step S2 to magnetize it into ferromagnetic particles p.

[0047] In the dispersion step S1, the viscoelastic material e and the ferromagnetic particles p before hardening are mixed and placed in a specified container (not shown), which is then placed in, for example, a vacuum degassing device "VD-VLH" manufactured by AS ONE Corporation. The silicone gel e and the magnetic particles p in the container are vacuum degassed, stirred, and mixed while a vacuum is drawn with a vacuum pump "G-50SA" manufactured by ULVAC Corporation.

[0048] In the curing step S2, the container is placed in a constant temperature dryer "ONW-300" manufactured by AS ONE Corporation, and the silicone gel is cured in the container which serves as a mold.

[0049] In this test, the shape of the secondary precursor was determined in the curing step S2, and as a result, the "magnetorheological body 1 in a formed state" of the present invention was obtained. However, it is also possible to obtain the magnetic viscoelastic body 1 by molding (e.g., cutting) the material into a shape suitable for the power generating device 100 after the hardening step S2, without determining the shape of the material in the hardening step S2, or before or after the magnetizing step S3.

[0050] In the above curing step S2, when the magnetic viscoelastic body 1 is formed into a cylindrical shape with an outer diameter of about 18 mm and a height of about 18 mm, the heating temperature and the heating time (curing time) are 60 to 80° C. and 20 to 40 minutes.

[0051] Fig. 3 shows the dispersion state of ferromagnetic particles p in the magnetically hard viscoelastic material s obtained by the first manufacturing method. The figure is a schematic enlarged view of a part of the material s (same as Fig. 6). As can be seen from the figure, the ferromagnetic particles p are uniformly and randomly dispersed in the viscoelastic material e.

[0052] In the magnetization step S3, a pulsed high magnetic field is applied to the secondary precursor obtained in the hardening step S2. For example, a pulse excitation type magnetic property measuring device "TPM-2-08s25VT-C" manufactured by Toei Kogyo Co., Ltd. is used to apply a high magnetic field to the compact 20. This device has a sample chamber that contains the secondary precursor, a superconducting coil surrounding the sample chamber, a capacitor and a switch connected in series to the superconducting coil, and a DC power source for charging the capacitor. When the switch is closed after charging the capacitor with the switch open, the discharge current of the capacitor flows in a flash into the superconducting coil, generating a uniform high magnetic field around the superconducting coil, i.e., in the sample chamber. In the magnetization step S3, in addition to such a pulse excitation type magnetic property measuring device, a vibrating sample magnetometer (VSM) and an electromagnet can also be used. Specifically, the applied magnetic field during magnetization was 8T.

[0053] 2.2 Second manufacturing method As shown in FIG. 4, the manufacturing process of this embodiment follows the following sequence. a Dispersion process S10 Ferromagnetic particles p, mainly composed of rare earth and having an average particle size of 100 μm or less, are dispersed in a viscoelastic material e before hardening treatment to obtain a primary precursor. The configuration of the device used in this dispersion step S10 is the same as that of the dispersion step S1. b Magnetization hardening process S20 A magnetization process in which a uniform magnetic field is applied to the primary precursor obtained in the dispersion step S10 to magnetize the ferromagnetic particles, and a hardening process in which the primary precursor is hardened are carried out simultaneously or sequentially.

[0054] Specifically, the magnetization hardening process S20 comprises a preliminary magnetization hardening completion process S21 in which magnetization and hardening processes are performed simultaneously, and a main magnetization process S22 in which a magnetic field stronger than the magnetization magnetic field in the preliminary magnetization hardening completion process S21 is applied to the preliminary magnetization hardened body obtained through the preliminary magnetization hardening completion process S21 to complete the magnetization of the ferromagnetic particles.

[0055] In molding the magnetically hard viscoelastic material s, the shape of the primary precursor is determined in the above-mentioned magnetization and hardening step S20, almost similarly to the first manufacturing method described above. On the other hand, in the magnetization and hardening step S20, the shape of the material may not be determined, and after the step S20 is completed, the magnetic viscoelastic body 1 may be obtained by molding the material into a shape suitable for the power generating device 100.

[0056] FIG. 5 shows a schematic configuration of a magnetization hardening treatment device employed when carrying out the preliminary magnetization hardening completion step 21 in the second manufacturing method. In this preliminary magnetization hardening completion step S21, plate-shaped permanent magnets (neodymium magnets) 201 are placed above and below the primary precursor 10, and a uniform magnetic field of 1.0 T or less (preferably about 0.01 to 1.0 T, specifically 0.1 T) is applied to the primary precursor 10. In the figure, 202 is a support, and the primary precursor-magnet integrated product 200 thus configured is stored in a temperature-controlled room 203, where the hardening of the viscoelastic material e can be carried out. The temperature-controlled chamber 203 used was the dryer previously described in the curing step S2 of the first manufacturing method.

[0057] When the magnetic viscoelastic body 1 has a cylindrical shape with an outer diameter of about 18 mm and a height of about 18 mm, the heating temperature and heating time (curing time) are 70 to 90° C. and about 20 to 40 minutes. The magnetic field applied in the main magnetizing step S22 was 8 T. The main magnetizing step S22 can be performed in substantially the same manner as the magnetizing step S3 in the first manufacturing method.

[0058] The resulting material structure, as shown diagrammatically in Figure 6, is a columnar structure (the inventors call these columns "clusters") in which ferromagnetic particles p are aligned in the vertical direction (C axis) of the figure, which is the direction of magnetization. As a result, this material has viscoelasticity, but when viewed as a whole viscoelastic body, it has a strong coercive force and the magnetic flux distribution formed around it has extremely high directionality. The "high coercive force material with viscoelasticity" obtained in this way is a new magnetically hard viscoelastic material s newly created by the inventors.

[0059] Furthermore, in the above preliminary magnetization hardening completion step S21, if the hardening direction and hardening time are appropriately controlled, the growth of the columnar structure and hardening can be synchronized. For example, hardening can be slowly advanced from bottom to top, and ferromagnetic particles p can be added to the silicone gel in small amounts to continuously mix, disperse, orient, and harden. The inventors call this slow mixing, disperse, orient, and harden process "small amount continuous hardening process" and the product thereof "continuous columnar cluster structure."

[0060] The previously explained Figures 3 and 6 are schematic diagrams of the case where the ferromagnetic particles p are magnetically isotropic. In contrast, Figures 14 and 15 show schematic diagrams of the case where the ferromagnetic particles p have magnetic anisotropy. These schematic diagrams will be explained after the power generation test results.

[0061] 3.Power generation test of power generation devices 3.1 Test equipment for the power generating device 100 FIG. 7 shows the configuration of a test apparatus 101 used for testing the performance of the power generating device 100 (specifically, the magnetorheological body 1) constructed as described above. The testing device 101 is configured with a sample placement section 101a on which a magnetorheological body 1 (sample) is placed while being sandwiched between a pair of pistons P, and a drive conversion mechanism 101c that converts the rotational motion of a motor 101b, which is a rotation drive device, into a reciprocating motion. The up and down motion obtained from the drive conversion mechanism 101c is transmitted to the sample 1. The drive of the motor 101b is controlled by a motor controller MC via a motor driver MD.

[0062] With this configuration, by placing the sample 1 on the sample placement section 101a, the sample 1 can be deformed periodically in the up and down direction. It is also possible to adjust the amount of deformation given to the sample 1 (by changing the drive conversion mechanism 101c) and the period of deformation (by changing the rotation speed of the motor 101b). The deformation given to the sample 1 is detected as the amount of deformation by a deformation amount detection device 101d. As the deformation amount detection device 101d, a laser displacement meter LDM is provided for the lower piston P, and a dynamic strain meter RCM is provided for the upper piston P via a load cell RC, to ensure detection accuracy.

[0063] A coil 101e is arranged around the outer circumference of the sample placement part 101a, and a detection mechanism 101f is provided to detect the induced current generated in the coil 101e. The cylindrical magnetic viscoelastic body 1 described in paragraphs

[0057] and

[0066] is used as a sample, and the coil 101e is made of a copper wire with a wire diameter of 0.5 mm, wound in a multiple-winding manner with an inner diameter of 36 mm and an outer diameter of about 50 mm, with 1400 turns. In the figure, A is a synchronization amplifier.

[0064] As a result, the sample, which is the magnetorheological body 1, is deformed, and a change in magnetic flux that occurs with this deformation becomes an induced current, which is detected in the form of a voltage by the detection mechanism 101f.

[0065] 3.2 Power generation device performance test results 3.2.1 Results using magnetically isotropic ferromagnetic particles The specifications of the magnetorheological body 1 used in the test are summarized below.

[0066] a. Magnetorheological material 1 Shape: Cylinder Cylinder diameter 18mm, cylinder height 18mm Material: Magnetically hard viscoelastic material obtained through the first and second manufacturing methods in the manufacturing process section. Viscoelastic body e: Silicone gel Ferromagnetic particles p: NdFeB magnetic powder with an average particle size of 5 μm. Ratio of ferromagnetic particles p (weight Wng) to viscoelastic body e (weight Wc) Weight%〔Wng / Wc×100%〕 50wt%, 60wt%, 70wt%, 80wt%, 90wt%

[0067] Elastic modulus: Approximately 10 to 80 kPa Residual magnetic flux density: about 0.04~0.4 T Coercive force: about 0.08~0.25 MA / m

[0068] b. Test conditions Deformation of magnetorheological body 1 Form: Compressive deformation at a predetermined cycle using a test device 101 Deformation: 0~10mm Deformation cycle: 1Hz to 10Hz, but confirmed up to 50Hz

[0069] Test results The results of the power generation test are shown in Figs. 8 to 10 show the results of electromotive voltage when the amount of deformation and compression was changed, and FIG. 11 shows the results of maximum power. In these figures, "with clusters" indicates the results of the second manufacturing method, and "without clusters" indicates the results of the first manufacturing method.

[0070] Electromotive force In Figures 8 to 10, the horizontal axis indicates the deformation compression amount [mm], and the vertical axis indicates the electromotive force [V]. In these figures, the blending ratio [wt%] of ferromagnetic particles p to viscoelastic material e is different between (a) and (b). The correspondence between the line type and the test conditions (deformation frequency [Hz], first manufacturing method, second manufacturing method are different) is shown at the bottom of the figure.

[0071] On the other hand, Figures 11(a) and (b) show the relationship between the frequency and maximum power of the deformation compression for different blend ratios [wt%] of ferromagnetic particles p to viscoelastic material e. In the figure, the horizontal axis shows the deformation frequency [Hz], and the vertical axis shows the maximum power [μW].

[0072] As can be seen from Figures 8 to 10, good power generation was achieved in the tested deformation compression range of 6 to 10 mm. As a result, the power generation amount was larger at higher frequencies and higher blend ratios. Regarding the amount of deformation, considering that the height of sample 1 is 18 mm, the rigidity of the material is low, so large deformation can occur. In the case of compressive deformation, it is preferable for the strain [deformation compression amount / material length before compression] to exceed 0.5 in the power generating device of the present invention. Regarding the deformation frequency, tests were carried out up to 50 Hz, which is beyond the stated range, and power generation performance was demonstrated up to this frequency. Furthermore, with regard to the blending ratio of ferromagnetic particles, the higher the ratio, the better the power generation performance. The inventors have confirmed that electricity is generated similarly when the blending ratio is 40 to 90 wt %.

[0073] In comparing the first and second production methods, the second production method showed higher power generation performance.

[0074] Now, looking at the results shown in Figure 11, it can be confirmed that the power generation output increases in proportion to the square of the frequency. In addition, in comparing the first and second manufacturing methods, the second manufacturing method showed higher power generation performance.

[0075] Furthermore, the state of the surface magnetic flux density that changes around the magnetorheological body 1 as a result of such deformation and compression operation is shown in the grayscale image in Fig. 12. The right side of each figure is the scale of the surface magnetic flux density [mT]. In (a), the outline of the magnetorheological body 1 in a free state is shown surrounded by a solid thick line. In (b), the magnetorheological body 1 in a state of being compressed by an aluminum plate as an external force transmission member 2 is shown in a solid thick thick drum shape.

[0076] As a result, it is found that the magnetic flux, which was concentrated above and below the magnetorheological body 1, is largely dispersed and reduced as the body is deformed by being subjected to large compression. This is a good result for a power generation device.

[0077] 3.2.2 Results using ferromagnetic particles with magnetic anisotropy The specifications of the magnetorheological body 1 used in the test are summarized below.

[0078] a. Magnetorheological material 1 Shape: Cylinder Cylinder diameter 18mm, cylinder height 18mm Material: Magnetically hard viscoelastic material obtained through the first and second manufacturing methods in the manufacturing process section. Viscoelastic body e: Silicone gel (same as in the case of magnetic isotropy) Ferromagnetic particles p: Anisotropy of NdFeB magnetic powder with average particle size of 5 μm Ratio of ferromagnetic particles p (weight Wng) to viscoelastic body e (weight Wc) Weight%〔Wng / Wc×100%〕 47wt%, 66wt%, 77wt%

[0079] Elastic modulus: Approximately 10 to 80 kPa Residual magnetic flux density: about 0.04~0.4 T Coercive force: about 0.08~0.25MA / m

[0080] b. Test conditions Deformation of magnetorheological body 1 Form: Compressive deformation at a predetermined cycle using a test device 101 Deformation: 0~10mm Deformation cycle: 1Hz to 10Hz, but confirmed up to 50Hz

[0081] Test results The results of the power generation test are shown in Figure 13(a)(b)(c). FIG. 13 shows a comparison between the first and second manufacturing methods when ferromagnetic particles p having anisotropy are used.

[0082] Electromotive force In Figure 13, the horizontal axis indicates the deformation period [Hz], and the vertical axis indicates the electromotive force [V]. In these figures, the blending ratio [wt%] of ferromagnetic particles p to viscoelastic material e differs between (a), (b), and (c). The blending ratio [wt%] is shown on each figure, and the corresponding relationship between the line type and the first and second manufacturing methods is shown. That is, the results according to the first manufacturing method are shown with solid lines, and the results according to the second manufacturing method are shown with dashed lines.

[0083] From the results shown in Figure 13, it can be seen that the electromotive force increases with the increase in the deformation period. In addition, in comparing the first and second manufacturing methods, the second manufacturing method was able to obtain a larger electromotive force when the compounding ratio was low or in the target medium range. Regarding the blending ratio [wt %] of the ferromagnetic particles p to the viscoelastic material e, when the ferromagnetic particles p were magnetically anisotropic, the highest was 66 wt % as shown in (b).

[0084] No significant difference in electromotive force was observed between the cases where the ferromagnetic particles p were "magnetically isotropic" and "magnetically anisotropic." However, the magnetically anisotropic ferromagnetic particles p are advantageous in terms of reducing the amount of the ferromagnetic particles p and maintaining the viscoelasticity of the viscoelastic body.

[0085] Figures 14 and 15 show the state of the magnetic moment in the first and second manufacturing methods when the ferromagnetic particles p are anisotropic. In these figures, the arrows drawn inside the particles p indicate the direction of the magnetic moment. In the first manufacturing method, the particles are not oriented uniformly, so the magnetic viscoelastic body 1 as a whole also exhibits isotropy. In contrast, in the second manufacturing method, the particles are oriented in a certain direction, so the magnetic viscoelastic body 1 as a whole also exhibits anisotropy. The formation of clusters can be controlled by the strength of the applied magnetic field and the hardening state of the viscoelastic material.

[0086] [Another embodiment] (1) In the above-described example, a basic unit of the power generating device 100 according to the present invention is shown. When actually constructing a power generating apparatus (not shown), a plurality of power generating devices 100 serving as basic units can be arranged in any positional relationship (for example, a plurality of power generating devices 100 arranged horizontally or diagonally). The cross-sectional shape, width, and height of the power generating device 100 can also be selected arbitrarily. In this way, when a plurality of power generating devices 100 are combined, the external force transmission member 2 may be common to the plurality of devices, or may be independent for each device. Furthermore, the coils 3 may be connected in parallel or in series. However, the directions of the induced currents must be aligned. Furthermore, the shape (three-dimensional shape) of the magnetorheological body 1 can be any shape such as a cylindrical shape, a rectangular column shape, a drum shape, or the like, depending on the purpose of use.

[0087] (2) In the embodiments described so far, silicone gel has been given as an example of a viscoelastic material. However, any material that can maintain a certain degree of shape retention (formability) upon hardening and has viscoelasticity at room temperature can be used as this type of viscoelastic material. Silicone gel (an example of a silicone-based elastomer) is an example of a thermosetting viscoelastic material (thermosetting elastomer) that hardens when heated. Viscoelastic materials (elastomers) that can be used in the present invention include at least one of silicone-based elastomers, styrene-based elastomers, olefin-based elastomers, urethane-based elastomers, and ester-based elastomers.

[0088] (3) In the embodiments described above, neodymium magnet particles have been used as an example of ferromagnetic particles, but ferromagnetic particles mainly composed of rare earth elements can be used as this type of material, such as SmFeN magnet particles and SmCo magnet particles.

[0089] In addition, the particle diameter can be set to a diameter that is preferable for uniform dispersion inside a viscoelastic material. As explained above, the inventors' study has shown that a diameter of 100 μm or less is preferable, and considering uniform dispersion, a diameter of 30 μm or less is more preferable from experience. The lower limit is about 1 μm.

[0090] (4) When manufacturing the magnetically hard viscoelastic material by the second manufacturing method shown above, a magnetization hardening process is carried out after the dispersion process, and the magnetization hardening process further includes a preliminary magnetization hardening completion process and a main magnetization process. The reason for using such a two-stage structure is to achieve good formation of a columnar structure, but for example, if the generation of the columnar structure and the magnetization of the ferromagnetic particles can be achieved simply by simultaneously carrying out the magnetization treatment and the hardening treatment, it is also possible to only carry out the simultaneous treatment. On the other hand, when the movement of the ferromagnetic particles within the viscoelastic material is restricted to a certain degree, the material may be subjected to a magnetizing process, a hardening process, and a further magnetizing process.

[0091] In addition, the magnetization operation in the preliminary magnetization hardening completion step in the second manufacturing method is configured as shown in FIG. 5, but the magnetization effect can be significantly improved by providing a so-called back yoke (iron magnetic flux control plate) on the outside (outside in the vertical axial direction) of the plate-shaped permanent magnet 201 (neodymium magnet plate) that is provided in a position to sandwich the primary precursor 10 from above and below.

[0092] (5) By using the power generation device of the present invention, it is possible to construct a vibration power generation facility that does not require the application of an external magnetic field, which makes it possible to apply it to energy harvesting, which converts energy that is normally wasted, such as energy generated when people walk, when cars run, or when buildings and other structures vibrate, into electrical energy. For generating electricity when people walk, it can be used in the soles of shoes. For generating electricity when a car runs or when vibrations occur in structures such as buildings, it can be used as a power generation facility that also serves as a damper placed in the foundations of bridges and buildings. The power generation device of the present invention is particularly effective for vibrations of low frequencies: 50 Hz or less (preferably 10 Hz or less), so it can be used in a frequency range lower than the frequency range that has been used so far. [Explanation of symbols]

[0093] 1. Magnetorheological material 2 External force transmission member (magnetic viscoelastic deformation means) 3 Coil (Means for generating induced current) 4 Connection wire (output means) 5. Load 10 Primary Precursors 101 Test Equipment 101a Sample placement section 101b Motor (rotary drive device) 101c Drive conversion mechanism 101d Deformation detection device 101e Coil (induction current generating means) 101f Detection mechanism 201 Neodymium magnets (permanent magnets) 202 Support s Magnetically hard viscoelastic material p ferromagnetic particles e Viscoelastic materials F External force

Claims

1. a magnetic viscoelastic body having a coercive force, the magnetic viscoelastic body being formed by molding a magnetically hard viscoelastic material in which magnetized ferromagnetic particles are dispersed within the viscoelastic material; a magnetic viscoelastic body deformation means for deforming the magnetic viscoelastic body by receiving an external force; an induced current generating means for generating an induced current therein by a magnetic flux whose spatial distribution changes due to the deformation of the magnetic viscoelastic body; an output means for outputting the induced current generated by the induced current generating means, the ferromagnetic particles are ferromagnetic particles mainly composed of rare earth elements, the viscoelastic material is a polymer material that contains the ferromagnetic particles as columnar structures aligned in the magnetic flux direction and exhibits viscoelasticity at room temperature, A method for using a power generating device, the blending ratio of the ferromagnetic particles to the viscoelastic material being within a range of 40 to 70 wt %, comprising: A method for using a power generating device, which generates power by periodically deforming the magnetorheological material through the magnetorheological material deformation means using an external force that varies with a period of 50 Hz or less.

2. The ferromagnetic particles are neodymium magnet particles with an average particle size of 100 μm or less, 2. The method for using a power generating device according to claim 1, wherein said induced current generating means is a coil.

3. 3. A method for using the power generating device according to claim 1 or 2, wherein the ferromagnetic particles have magnetic anisotropy.

4. a dispersion step of dispersing ferromagnetic particles having an average particle size of 100 μm or less, mainly composed of rare earth elements, in a viscoelastic material before a curing treatment to obtain a primary precursor; the magnetization hardening process includes a preliminary magnetization hardening completion process in which the magnetization process and the hardening process are simultaneously performed in a magnetization process in which plate-shaped permanent magnets are placed above and below the primary precursor obtained in the dispersion process, and a uniform magnetic field of 0.01 to 0.1 T is applied to the primary precursor to magnetize the ferromagnetic particles, and a hardening process in which the primary precursor is hardened; and a main magnetization process in which a magnetic field stronger than the magnetization magnetic field in the preliminary magnetization hardening completion process is applied to the preliminary magnetization hardened body obtained through the preliminary magnetization hardening completion process to complete the magnetization of the ferromagnetic particles, A method for producing a magnetically hard viscoelastic material comprising the ferromagnetic particles as columnar structures aligned in the direction of magnetic flux.

Citation Information

Patent Citations

  • Magnet motor

    JP2000341916A

  • Actuator driven by magnetic force, drive unit using the actuator, and sensor

    JP2009165219A

  • Rod-like bond magnet and method for manufacturing the same

    JP2011129586A

  • Magnetic viscoelastic body and method of manufacturing the same

    JP2016152337A

  • Bond magnet and manufacturing method of bond magnet

    JP2016192517A